Demographic Factors and Job Characteristics Associated With Burnout in Chinese Female Nurses During Controlled COVID-19 Period: A Cross-Sectional Study - Zhou, Li-Li; Zhang, Shu-E; Liu, Jiao; Wang, Hong-Ni; Liu, Li; Zhou, Jing-Jing; Bu, Zhi-Hua; Gao, Yu-Fang; Sun, Tao; Liu, Bei (Frontiers in Public Health, 2022)
Background: To investigate the prevalence of burnout syndrome among Chinese female nurses during controlled COVID-19 period and explore its associated socio-demographic factors and job characteristics. Methods: With the multistage, stratified sampling method, a cross-sectional online survey was conducted from September to October 2020 in China. The survey tool included revised Maslach Burnout Inventory (MBI) with 15 items, socio-demographic and job characteristics. Using univariate logistic regression analysis and multivariate factor logistic regression analysis to identify the risk factors for burnout of female nurse. Results: During controlled COVID-19 period in China, the overall prevalence of burnout symptoms among Chinese female nurses was 60.2% with a breakdown in severity as follows: 451 (39.8 %) mild, 163 (14.4%) moderate and 68 (6.0%) severe burnout. Little variance was reported for burnout symptoms according to job tenure (Waldχ2 = 14.828, P < 0.05, OR < 1), monthly salary income (Waldχ2 = 12.460, P < 0.05, OR < 1), and night shift (Waldχ2 = 3.821, P < 0.05, OR > 1). Conclusion: Burnout symptoms among Chinese female nurses were prevalent and associated with job tenure, monthly salary income, and night shift. Female nurses who were with shorter job tenure, worked at night shifts, and lower monthly salary tended to exhibit increasing high-level burnout than their counterparts. This study serves as an implication for administrators and policy-makers to improve nurses’ work conditions for promoting overall healthcare service quality.